Iron deficiency anaemia in childhood and thyroid function - Tienboon P. (2014)
Studies in animals and adults have indicated iron deficiency anaemia to be associated with altered thyroid hormone metabolism. The aim of the present study was to determine the effect of iron deficiency anaemia on the thyroid function of young children. Concentrations of thyroxine (T4) and triiodothyronine (T3), free thyroid hormones (fT4 and fT3), thyroxine binding globulin (TBG), and thyroid stimulating hormone (TSH) were measured in the basal state and in response to an intravenous bolus of thyrotropin releasing hormone (TRH) in nine children one to three years of age with iron deficiency anaemia (IDA) before and after treatment with oral iron. The results of the anaemic children were also compared to basal and stimulated concentrations of thyroid hormones, TBG, and TSH of eight iron sufficient, age-matched children. Seven of the IDA and 6 of the control children were male. The mean haemoglobin (Hb) and serum ferritin (SF) in the IDA children at baseline were 93 g/L (range 81-102) and 6 μg/L (range 1-12) which increased to 121 g/L (range 114-129) and 54 μg/L (range 19-175), respectively, after a mean of 2.3 months (SD 0.5) of iron therapy. In the control group, mean Hb and SF were 125 g/L (range 114-130) and 51 μg/L (range 24-144), respectively. The basal values of TBG and thyroid hormones of the IDA children before and after iron treatment were not different from the control children. Similarly, there was no statistical difference in the thyroid hormones in the IDA children before compared to after resolution of the anaemia. Compared to the control children, the TSH response over time to TRH, TSH area under the curve (TSHAUC), and the peak TSH value after stimulation were all lower in the IDA children both before and after resolution of anaemia, but the differences were not significant. Iron therapy and resolution of anaemia had no effect among the IDA children. The time to reach the peak TSH concentration was longer in the IDA children (P = 0.08) than the control children before iron therapy. While the time to peak TSH decreased upon resolution of the anaemia, the difference was not significant. There was no effect of Hb concentration, age, or anthropometry with TSH, TSHAUC, or time to peak TSH after TRH stimulation in the IDA children before treatment. Normal thyroid function was preserved in these children with iron deficiency anaemia, however three of nine children had minor abnormalities of hypothalamic-pituitary function. These results indicate that hypothyroidism is unlikely to be a major cause of impaired psychomotor development or growth in young children with iron deficiency anaemia.